Multistepped Drill Design for Single‐Stage Implant Site Preparation: Experimental Study in Type 2 Bone. (29th September 2014) - Abboud, Marcus; Delgado‐Ruiz, Rafael Arcesio; Kucine, Allan; Rugova, Sihana; Balanta, Julian; Calvo‐Guirado, Jose Luis
Abstract: Purpose: To evaluate an experimental multistepped drill for single‐stage implant site preparation by means of real‐time analysis of thermal variations during and postdrilling, and by implant stability evaluation. Materials and Methods: Temperature and time were recorded in real time by paired microprobe thermocouples during simulated osteotomy in type 2 bone similes at the cortical and cancellous zones. Three different drilling groups with a new multistepped drill design were compared: Control (2‐mm diameter pilot drill + 3.3‐mm three‐stepped drill + 4.1‐mm three‐stepped drill); Test A (3.3‐mm three‐stepped drill); and Test B (4.1‐mm three‐stepped drill). Implants were inserted, and implant stability was evaluated with the Perio Test Value (PTV). Two‐wayanova was used to test the independent effects of osteotomy and implant diameter on temperature and stability. Results: All the drills induced thermal changes without significant differences between groups ( p > .05). Drilling in cortical bone produced significant increase of the temperatures in a range of 1.8 ± 0.9°C compared with drilling in cancellous bone ( p < .05). ΔT temperatures were significantly higher for test groups in cortical and cancellous bone ( p < .05); ΔT10 for all groups showed a reduction of the temperature in a range of 1.7 ± 0.3°C without significant differences between groups ( p > .05); the mean time to accomplish drilling was significantly longer in the control group ( p < .05); test groups took 10 ± 0.3 seconds less to reach the required drilling depth. PTV values were higher in test groups compared with controls ( p < .05). Conclusions: The multistepped drills used for single‐stage implant site preparation Increase temperature as in comparison with a conventional incremental protocol; Induce the temperature increment in cortical bone compared with the cancellous bone; Reduce drilling time when a multistepped drill is used alone; and Increase implant stability twofold compared with a conventional incremental protocol.